2020
DOI: 10.1111/avj.13008
|View full text |Cite
|
Sign up to set email alerts
|

Faecal PCR panel results and clinical findings in Western Australian dogs with diarrhoea

Abstract: Aim To describe faecal PCR (fPCR) results and clinical findings of dogs seen at a university teaching hospital for diarrhoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…Faecal samples were solicited from different geographically dispersed veterinary laboratories in the US. This study confirmed statistically higher prevalence in diarrheic dogs (3.8%) than in non-diarrheic dogs (1.8%) [104], which is in concordance with other reports [8,[105][106][107]. Faecal samples collected from 144 nondiarrhoeic dogs in Grenada revealed that 5.6% (8/ 144) of them were Salmonella positive [105].…”
Section: Salmonella Spp Prevalence In Dogssupporting
confidence: 92%
See 1 more Smart Citation
“…Faecal samples were solicited from different geographically dispersed veterinary laboratories in the US. This study confirmed statistically higher prevalence in diarrheic dogs (3.8%) than in non-diarrheic dogs (1.8%) [104], which is in concordance with other reports [8,[105][106][107]. Faecal samples collected from 144 nondiarrhoeic dogs in Grenada revealed that 5.6% (8/ 144) of them were Salmonella positive [105].…”
Section: Salmonella Spp Prevalence In Dogssupporting
confidence: 92%
“…Braenderup (2/27, 7%) S . Infantis (2/27, 7%) [ 102 ] 5.4% 22 Australia 2019 405 Not specified [ 107 ] 5.6% 8 Grenada, West Indies 2018 144 6 Salmonella enterica serovars, 35 isolates S . Arechavaleta (13/35, 37.1%) S .…”
Section: Salmonella Spp Prevalence In Dogsmentioning
confidence: 99%
“…All reports originate from the eastern states of Australia, with none reported in WA. The seven cases of CDV detection were comparable to prior fPCR data from WA dogs 7,8 . Vaccine cross‐reactivity is the most likely cause, however, detailed clinical data (particularly clinical signs and vaccination status) would be required to evaluate this further.…”
Section: Figuresupporting
confidence: 56%
“…Given the reported significance of geographic variation, 5 establishing a regional enteric organism profile may help veterinarians interpret fPCR results, and facilitate more informed comparison of studies from different geographic regions. A few studies describe fPCR results of dogs in Australia, however these are either not restricted to WA, 6,7 or present a small dataset from a single WA institution 8 . None of these studies explored seasonal or regional patterns.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation